Investigation of Hydrological Droughts in the Eastern Mediterranean Basin Using Hybrid Trend Analysis Methods - Alashan, Sadık; Gül, Enes; Toprak, Ahmet; İkinciogullari, Erdinc (My University, 2025)
This study investigates the impact of climate change on river systems within the Eastern Mediterranean Basin (EMB), utilizing the Mann-Kendall (MK) test, enhanced by Sen’s slope estimator (SSE) and Şen’s Innovative Trend Analysis (ITA) methods. The research focuses on hydrological changes, particularly in streamflow trends, and examines their implications in the context of climate change and anthropogenic activities. The methodology involves a detailed analysis of hydro-meteorological series, including streamflow data from different observation stations. The research enhances the robustness of trend detection by applying advanced methodologies such as trend-preserving pre-whitening, which satisfies the serial independence requirement of the MK test. The study area comprises 10 sub-basins in the EMB, with a particular attention to the Göksu River and its tributaries. The results reveal significant declines in the annual streamflow values at several stations, demonstrating the considerable influence of climate and environmental changes on the basin's hydrology. These findings are further evaluated using ITA graphs, which offer a detailed analysis of the spatial and temporal variability in streamflow patterns. This research contributes to a better understanding of hydrological responses to climatic variability, providing vital information for water resource management and policies in regions undergoing significant environmental changes.
Keywords: Trend; Mann-Kendall Test; Streamflow; Eastern Mediterranean Basin; Sen’s Slope Estimator; Şen’s Innovative Trend Analysis